Mediastinitis as a complication of Epstein-Barr virus infection: a rare entity - Younus, Shifa; Maqsood, Hamza; Younas, Amna (International Journal of Research in Medical Sciences, 2020)
Epstein-Barr virus (EBV) is a member of the herpes virus family that can infect humans. Common manifestations of Epstein-Barr virus infection include fever, lymphadenopathy and pharyngitis with some rare complications including mediastinitis, myocarditis, pancreatitis, acute kidney failure and neurological disorders. Clinical findings along with serological evidences are needed to diagnose the infection. Early investigation for EBV in febrile patients can expedite both diagnosis and treatment.